Biological Relatives : IVF, Stem Cells, and the Future of Kinship - Franklin, Sarah, 1960- (Book collections on Project MUSE., 2013)
Sarah Franklin explores the history and future of in vitro fertilization (IVF) thirty-five years and five million babies after its initial success as a form of technologically-assisted human reproduction.